Unraveling the Profitability Puzzle: Exploring the Dynamics of Firm Value in Indonesian Real Estate Enterprises - Sholikha Oktavi Khalifaturofi'ah; Titis Puspitaningrum Dewi Kartika; Rohmad Fuad Armansyah (APMBA (Asia Pacific Management and Business Application), 2024)
The purpose of this study is to explore the intricate relationship between profitability and firm value in the context of Indonesian real estate enterprises. Utilizing a panel data methodology, this research draws from financial data spanning six years (2017-2022) of 21 Indonesian real estate firms. The analysis employs a robust random effect model for data exploration. The empirical findings unveil crucial connections between profitability and firm value in the Indonesian real estate realm. Notably, a significant negative correlation emerges between profitability and firm value, indicating that higher profitability does not guarantee higher firm value. Additionally, firm size exerts a dampening effect on firm value. Conversely, total asset growth and turnover prove to be influential drivers of firm value, underscoring the importance of robust asset growth and turnover. This study contributes by delving into the profitability-firm value relationship unique to Indonesia's real estate sector.